IMPLEMENTASI KEBIJAKAN PENDIDIKAN INKLUSIF UNTUK ABK DI SURABAYA - Ika Devy Pramudiana (JURNAL DIMENSI PENDIDIKAN DAN PEMBELAJARAN, 2017)
Education is one of important aspect of human life. A good education will produce smart and competent nation’s next generation. Education is a human right, with no exception for children with disabilities (difable). Schools as environment have an important role need supports from all parties. Role of Parents, school special, expert, high school, SLB, and the government is still rated low. The school as a means and infrastructure is still limited. Involvement of parents as one of key to the success of inclusive education should be built well. Unfortunately, there are still some obstacle ad practical depreciation and conditions, infrastructure, and the financial conditions.Key words: inclusive education, disable students, policy